2020
DOI: 10.1073/pnas.2009506117
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy increases resistance to chemotherapeutics by antagonizing cell division

Abstract: Aneuploidy, defined as whole chromosome gains and losses, is associated with poor patient prognosis in many cancer types. However, the condition causes cellular stress and cell cycle delays, foremost in G1 and S phase. Here, we investigate how aneuploidy causes both slow proliferation and poor disease outcome. We test the hypothesis that aneuploidy brings about resistance to chemotherapies because of a general feature of the aneuploid condition—G1 delays. We show that single chromosome gains lead to increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 65 publications
4
45
0
Order By: Relevance
“…In C. albicans , as well as in many other organisms, aneuploidy is a prevalent strategy of stress adaptation ( 59 , 60 ; reviewed in references 61 64 ). Specifically, aneuploidy is often a rapid mechanism of adaption to antifungal stress ( 11 13 , 16 , 17 ; reviewed in reference 65 ) and also facilitates adaptation to other stresses in vitro , e.g., alternative carbon sources ( 66 68 ; reviewed in reference 69 ), and in vivo , e.g., passage in mouse blood ( 70 ), the oral cavity ( 71 , 72 ), and the gastrointestinal tract ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…In C. albicans , as well as in many other organisms, aneuploidy is a prevalent strategy of stress adaptation ( 59 , 60 ; reviewed in references 61 64 ). Specifically, aneuploidy is often a rapid mechanism of adaption to antifungal stress ( 11 13 , 16 , 17 ; reviewed in reference 65 ) and also facilitates adaptation to other stresses in vitro , e.g., alternative carbon sources ( 66 68 ; reviewed in reference 69 ), and in vivo , e.g., passage in mouse blood ( 70 ), the oral cavity ( 71 , 72 ), and the gastrointestinal tract ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, there are several ongoing efforts concentrated on understanding the contribution of cell-intrinsic factors-such as genetic alterations and epigenetic changes-as well as cell-extrinsic stimuli-such as cytokines and growth factors-as major players responsible for drug resistance (Vasan et al, 2019). Recent studies have identified an increased resistance of aneuploid cancer cell lines to multiple chemotherapies and to drugs in general (Cohen-Sharir et al, 2021;Replogle et al, 2020). However, very little is known about how and why aneuploidy and the ensuing genomic instability affects the therapeutic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of cancers have chromosome arm gains or losses 1 , a state called aneuploidy. Aneuploidy has been shown to contribute to tumor evolution [2][3][4] , drug resistance 3,[5][6][7][8][9] , and metastatic dissemination [10][11][12] . High levels of aneuploidy are also associated with poor patient survival 3,[13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%